Género y poder en Argentina. Las elites ejecutivas de Fernández de Kirchner, Macri y Fernández - Canelo, Paula Vera (2021)
The article analyzes the link between gender and power in the governmental elites of the National Executive during the presidencies of Fernández de Kirchner (2011), Macri (2015) and Fernández (2019) in Argentina. The systematic study of 857 ministers, secretaries and undersecretaries shows the degree of female participation, masculinization/feminization trends in management areas and agencies, and the relationship between position and gender, identifying which "glass ceilings" hinder parity.